Is China's outward investment in oil a global security concern? - Ilan Alon; Aleh Cherp (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
The dramatic increase in investment by Chinese SOEs in overseas oil assets is primarily driven by energy security concerns. Whether such investment will benefit or harm energy security of other countries is hotly contested. On one hand, this investment can supplement the overall lack of investment in the sector, benefiting all consumers. On the other hand, it may exacerbate environmental and political problems associated with fossil fuels.
Keywords: 330